Three-Dimensional Graphene-Decorated Copper-Phosphide (Cu3P@3DG) Heterostructure as an Effective Electrode for a Supercapacitor - Kumar, Subodh; Aziz, S. K. Tarik; Kumar, Sushil; Riyajuddin, Sk; Yaniv, Gili; Meshi, Louisa; Nessim, Gilbert D.; Ghosh, Kaushik (Frontiers in Materials, 2020)
Transition metal phosphides already emerged with great interest due to their energy storage capacitance, superior metalloid characteristics, and decent electrical conductivity. To achieve a commercially viable outcome, these electrodes are fabricated with interconnected carbonaceous materials. Herein, we have synthesized hexagonal copper phosphide (Cu3P) platelets using chemical vapor deposition (CVD) and integrated it with highly conducting three-dimensional graphene (3DG), leading to a nanohybrid (Cu3P@3DG) as a coulombic efficient supercapacitor. This nanohybrid has exhibited a specific capacitance (Csp) of 1,095.85 F/g at 10 mV/s scan rate along with a cycling stability of 95% capacitive retention after 3,000 cycles at a current density of 8.97 A/g. The Csp is almost four times higher and the stability is 1.2 times higher compared to the bare Cu3P platelets. We have fabricated an asymmetric supercapacitor (ASC) using Cu3P@3DG on graphite as cathode and activated carbon (AC) on graphite as anode (Cu3P@3DG//AC) that has shown high specific capacity (108.78 F/g), energy density (8.23 Wh/kg), and power density (439.6 W/kg). Moreover, this ASC has exhibited an excellent life cycle (5,500 consecutive charge–discharge with 96% coulombic efficiency). Therefore, the proposed all-solid-state hybrid device can be considered as a route for next-generation high-performing energy storage devices.